MEMAHAMI â€œMAKNA LAINâ€ INSENTIF TERHADAP KINERJA BANK YANG HOLISTIK: PERSPEKTIF INTERDISIPLINER - Leniwati, Driana (Univesitas Muhammadiyah Malang, 2019)
Theoretically, financial incentives motivate the employee to improve performance but also found empirical evidence that shows the financial incentives are often inversely proportional (Young and Lewis 1995; Jenkins et al 1998). Base on the phenomena is interesting to look more at the meaning of incentives for Customer Relationship Manager (CRM) in the performance improvements. This study uses an interdisciplinary perspective of management accounting, psychology, and spirituality and borrows psychological needs and spiritual theories to see the motivation of CRM in improving performance based on their needs. The method used is a case study with an interpretive approach. Qualitative data is obtained by conducting interviews with several CRM in one of a commercial bank. The results of this study found there are other meanings of incentives for CRM. These meanings are inclined about security, loyalty, and accountability for their work, the meaning of appreciation, self-actualization, and spiritual which defeats the meaning of basic needs. The meanings that arise not depending on the period of work or position but more on the awareness of each. Understanding these meanings can be taken into consideration in making the right incentive scheme for employees. So that, incentives can really motivate employees to improve their performance.